PENGARUH PELATIHAN ASERTIVITAS TERHADAP PENINGKATAN HARGA DIRI (EFFECTS OF ASSERTIVE TRAINING ON INCREASING THE LOW SELF ESTEEM) - Iriani, Niken (Indigenous, 1995)
Assertive training is the procedural training for helping people acquire appropriate emotional ekpressiveness in social and interpersonal situation.          This study investigated the effects of assertive training on increasing self esteem of student in  Indonesia.          Fourteen students participated in this study, 7 in experimental group and 7 in the control group. Self esteem scale was administered before and after the training.          The analysis of covariance was used to find out whether the Self Esteem Scales score differed before and after training. Result of these analysis showed that SESs score difference on after the training (P,0.002).          The result of this study showed that assertive training was effective on increasing the low self esteem. This study support the notion that assertiveness results in increased self respect and self confidence. It enhances sense of dignity as human beings.